Dietary strategies for chronic spontaneous urticaria: an evidence‐based review. (26th November 2021) - Podder, Indrashis; Jaiswal, Saurabh; Das, Anupam
Abstract: Although the relationship between diet and chronic spontaneous urticaria (CSU) remains elusive, several patients seek dietary modifications as they are easy and cost‐effective. Adequate patient education and counseling are crucial as modified diets may be beneficial for a subset of antihistamine refractory CSU patients, and no modality currently exists to identify these patients. Elimination of food items based exclusively on patient history may lead to unnecessary restrictions in most cases resulting in nutritional deficiencies and impaired quality of life. Several dietary strategies have been tried till date with varying rates of success and evidence. This review highlights the various dietary strategies along with their levels of evidence, which may help the treating dermatologists and physicians to counsel CSU patients and make evidence‐based treatment decisions. There is grade A recommendation for the elimination of food additives (artificial pseudoallergens), personalized diets, vitamin D supplementation, Diamine oxidase supplementation and probiotics (in children), grade B recommendation for dietary elimination of red meat, fish and their products, natural pseudoallergens (fruits, vegetables, and spices), and low‐histamine diet, while dietary elimination of gluten (with concomitant celiac disease) has grade C recommendation. Notably, elimination diets should be continued for at least 3 consecutive weeks to assess their effectiveness.